NEW RECORDS OF MIRIDAE (HETEROPTERA) IN SERBIA (Acta Entomologica Serbica, 2020)
Data on 9 new species for the fauna of Serbia are presented: Dicyphus (Dicyphus) epilobii Reuter, 1883; Europiella decolor (Uhler, 1893); Icodema infuscata (Fieber, 1861); Lygus wagneri Remane, 1955; Orthocephalus brevis Panzer, 1798; Phoenicocoris obscurellus (Fallén, 1829); Phytocoris (Exophytocoris) scitulus Reuter, 1908; Pinalitus rubricatus (Fallén, 1807) and Polymerus (Poeciloscytus) palustris Reuter, 1905.